Questioning in Teacher Talk - Cut Aulia Makhsum; Siti Sarah Fitriani; Usman Kasim (Proceedings of AICS - Social Sciences, 2016)
Asking questions is one of components in teacher talk. Some types of questions are posed by teachers to assess students’ understanding of learning materials. This paper presents the results of the investigation of the types of questions used by English as Foreign Language (EFL) teachers in teaching English for the second graders of a senior high school. The subject was a female teacher who teaches English at SMA Teuku Nyak Arif Fatih Bilingual School, Banda Aceh. This qualitative study was conducted employing six classroom observations (480 minutes) focusing on four types of questions (factual, empirical, productive and evaluative) based on Moore (2007). The results revealed that factual questions appeared to be the most dominant type employed by the teacher (59.9%), followed by evaluative (16.6%) and empirical (12.9%). Productive questions were the least occurrence from all types of questions applied, which is 10.7%.